Analysis of Holhymenia histrio genome provides insight into the satDNA evolution in an insect with holocentric chromosomes - Bardella, Vanessa Bellini [UNESP]; Milani, Diogo [UNESP]; Cabral-de-Mello, Diogo Cavalcanti [UNESP] (Springer Nature, 2020)
Satellite DNAs (satDNA) are fast-evolving repetitive sequences organized in large tandem arrays, with characteristic enrichment in heterochromatin. Knowledge about evolutionary dynamics of this genome fraction is mostly restricted to its characterization in species with monocentric chromosomes, i.e., localized centromeres. In holocentric species, with non-localized centromeres, satDNAs have been largely ignored. Here we advance the understanding of satDNA evolution among holocentric species by characterization of the most abundant satDNAs in the hemipteran Holhymenia histrio, integrating genomic and chromosomal analyses. High plasticity at chromosomal and molecular levels was noticed for 34 satDNAs populating H. histrio genome. One satDNA family in particular (HhiSat01-184) was highly amplified on multiple chromosomes and also highly polymorphic. Our data support the emergence of a new satDNA family from this abundant satDNA, confined to a single chromosome. Moreover, we present new information about composition of a peculiar chromosome in Coreidae, the m-chromosome, and of the X chromosome. Overall, the molecular and chromosomal patterns for satDNAs in the holocentric species H. histrio seem to be similar to those observed in monocentric species.
Keywords: Coreidae; Hemiptera; heterochromatin; repetitive DNAs